Homeless youth, strain, and justice system involvement: An application of general strain theory. (March 2016) - Snyder, Susan M.; Hartinger-Saunders, Robin; Brezina, Timothy; Beck, Elizabeth; Wright, Eric R.; Forge, Nicholas; Bride, Brian E.
Abstract: Using Agnew's (2006) general strain theory as a guide, we seek to identify some of the key events and experiences that place homeless youth at high risk of justice system involvement. By expanding and elaborating on the particular types of strains and stressors that are relevant to homeless youth, we identify several key (and understudied) strains that may help to account for their high risk of justice system involvement and that may also place them at risk of persistent homelessness. These strains include experiences of polyvictimization, experiences of discrimination and violent victimization that result from an LGBT identity, and a variety of failures and setbacks associated with multiple system involvement. The implications of this work for policy, practice, and future research are discussed. Highlights: Identifies pathways to homelessness among youth Discusses key federal policies that currently address homeless youth Applies Agnew's (2006) general strain theory to homeless youth Homeless youth are at a higher risk of justice involvement. Identifies various strains (e.g., polyvictimization) that contribute to offending